Designing a Digital Behavior Change Intervention for Online Grocery Stores: A Randomized Controlled Trial - Manzke, Leonie (CEUR Workshop Proceedings, 2025)
Consumers face an abundance of food choices that occur in complex "hyper-choice"environments, making it difficult for individuals to follow through on healthful intentions. With poor diets posing a leading global health risk, behavioral strategies in decision-making settings, such as grocery shopping, should be considered to encourage healthier habits. Limitations in previous research include small or contradictory effects, as well as challenges in applying findings to digital settings, which have become more relevant with the increased prevalence of online grocery shopping. This paper discusses the design and methodology of a randomized controlled trial in a simulated online grocery store that will integrate an intervention grounded in Fogg's Behavior Model. N=800 participants will complete a survey and shopping task, then repeat the task a week later, while being randomized into one of four groups: control, receiving real-time feedback, a personalized reflection prompt, or both. The number of fruit and vegetable portions selected will be the primary outcome. Findings will contribute to the theoretical understanding of food choice and inform the design of effective digital interventions in persuasive systems to promote healthier shopping behaviors.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Behavioral Interventions; Fogg Behavior Model; Food Choice; Online Grocery Stores; Persuasive Systems